The regional efficiency in the use of European agricultural funds in Spain: Growth and employment analyses - Blanco, M. (2021)
After World War II, the European Union launched the Common Agricultural Policy. Since then, this programme has been adapting to the new economic and social realities that the European agricultural sector has been going through. Currently, a large part of this programme has been financed with the European Agricultural Guarantee Funds and the European Agricultural Fund for Rural Development. Two packages of funds have been approved in recent decades: one for the 2007–2013 and another for the 2014–2020 periods. This research has had as its main objective to determine whether the Spanish regions maintain homogeneous levels of efficiency in the use of these resources in the management of agricultural programmes from a growth and employment perspective. A methodology that is frequently used by researchers in the efficiency analyses has been chosen: data envelopment analysis. Among the main conclusions obtained are that the efficiency in the management of agricultural funds is very uneven among the studied Spanish regions. Furthermore, these differences are maintained throughout the analysed periods. This study suggests changes and proposes criteria for the allocation of European resources to finance the projects presented by the Spanish regions.